2011
DOI: 10.4097/kjae.2011.61.5.372
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the intravenous phenylephrine on the level of spinal anesthesia

Abstract: BackgroundSpinal anesthesia causes hypotension and bradycardia due to sympathetic nerve block and it is difficult to predict the level of sensory block and the duration of blockade. Recent studies have reported that intravenous phenylephrine can reduce the rostral spread of spinal anesthesia in pregnant women. We think a phenylephrine infusion will be useful for maintaining the baseline blood pressure by reducing the rostral spread of spinal anesthesia during the elective surgery of non-obstetric patients.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…The rise in HR in Group E was more as compared to Group P. The results of this study were in accordance with the study of other investigators. They also reported higher incidence of bradycardia in patients receiving phenylephrine as compared with patients receiving ephedrine for prevention of hypotension during spinal anesthesia for caesarean section (21)(22)(23). On contrary to the results of the present study, Adigun et al found bolus IV phenylephrine 100µg to be as effective as ephedrine 5mg with no significant difference in HR between two groups and an equivalent hypotensive control.…”
Section: Discussioncontrasting
confidence: 95%
“…The rise in HR in Group E was more as compared to Group P. The results of this study were in accordance with the study of other investigators. They also reported higher incidence of bradycardia in patients receiving phenylephrine as compared with patients receiving ephedrine for prevention of hypotension during spinal anesthesia for caesarean section (21)(22)(23). On contrary to the results of the present study, Adigun et al found bolus IV phenylephrine 100µg to be as effective as ephedrine 5mg with no significant difference in HR between two groups and an equivalent hypotensive control.…”
Section: Discussioncontrasting
confidence: 95%
“…Despite the fact that the use of epinephrine is not associated with an elevated risk of TNS 15 , it has been linked to a case of cauda equina syndrome in one study 16 The usage of phenylephrine has been associated with an increased risk of TNS (10-fold increase) 17 .…”
Section: Discussionmentioning
confidence: 94%
“…The results of this study were in accordance with the study of other investigators in which they reported higher incidence of bradycardia in patients receiving phenylephrine as compared with patients receiving ephedrine for prevention of hypotension during spinal anesthesia for cesarean section. [ 10 11 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays spinal anesthesia is widely used for elective lower abdominal surgeries. [ 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 ] It is frequently accompanied by hypotension, which may be defined in absolute terms as a systolic blood pressure (SBP) less than 90 or 100 mmHg or in relative terms as a percentage (20% fall from baseline). [ 1 ] The severity of this hypotension depends on the height of the block, the position of the patient, and the volume status of them.…”
Section: Introductionmentioning
confidence: 99%